Effects of nutritional plans and genetic groups on performance, carcass and meat quality traits of finishing pigs - VELOSO,Rogério de Carvalho (2019)
Abstract We aimed to evaluate the effects of paternal genotypes (Piau, Duroc-based, and Pietrain) and nutritional plans with different digestible lysine contents (Low, Medium, and High) on performance, carcass, and meat quality traits of pigs. Pietrain and Duroc crossbred barrows and gilts were similar in performance and carcass traits and had the greatest values when compared to Piau crossbred pigs. Regarding meat quality, drip loss was greater in pork from Pietrain crossbred barrows and gilts compared to Duroc and Piau crossbred pigs. The High nutritional plan had the greatest daily digestible lysine intake value, followed by the Medium and Low nutritional plans. Most of the performance, carcass, and meat quality traits that were evaluated in barrows and gilts were not affected by the nutritional plans. In general, Duroc and Pietrain crossbred pigs had a greater performance and carcass yield when compared to Piau crossbred pigs.